Ideological and media discourse study of Nasrudin Joha's political article - Icol Dianto; Andi Faisal Bakti; Iding Rosyidin (Islamic Communication Journal, 2021)
Nasrudin Joha's ideology and discourse were one of the attempts to compensate for the dominance of rulers and capitalists. The criticism developed by Nasrudin Joha built the consciousness of the oppressed. With that awareness, Nasrudin Joha mobilized the oppressed to form a unified Islamic political identity and establish a caliphate system in Indonesia. This research aims to analyze Nasrudin Joha's strategy in building the ideology of the caliphate system and proclaiming it through social media. The authors used qualitative research methods in the field of mass media and used critical discourse analysis. The focus of his study was ideology and discourse in an article written by Nasrudin Joha on an online media platform. The results of this study found that Joha had used the theory of active reception to the readers. Joha positioned himself as the opposition and voiced the aspirations of the oppressed. In developing ideology and discourse about the caliphate system, Joha has similarities with the flow of Marxism, namely the resistance of the oppressed. On the other hand, Joha has a tendency to follow post-Marxist notions of freedom and oppose the oppression of the regime and capitalist groups.